The Effectiveness of Pictionary Game to Improve the Students Writing Skills - Yuanita, Rina (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2022)
This classroom action research study aimed to investigate the effectiveness of integrating the Pictionary game as an instructional tool to enhance students' writing skills among eighth-grade students at SMPN 15 Kabupaten Sorong. The sample consisted of 22 students, and the research design followed a classroom action research approach. The study utilized pretest, posttest Cycle 1, and posttest Cycle 2 assessments to measure students' writing proficiency. The results revealed a mean score of 65.48 in the pretest, which increased to 73.29 in posttest Cycle 1 and further improved to 82.47 in posttest Cycle 2. The progressive increase in mean scores indicated a significant enhancement in students' writing skills following the implementation of the Pictionary game intervention. The findings suggest that the interactive and engaging nature of the game positively impacted student engagement, motivation, and collaboration, leading to improved writing abilities over the course of the study. This study contributes to the growing body of research supporting the efficacy of incorporating educational games, such as Pictionary, in classroom instruction to promote skill development and academic achievement. The results underscore the potential of innovative pedagogical strategies in enhancing student learning outcomes and highlight the importance of dynamic and interactive approaches to teaching writing skills.